Post-Resettlement Socio-Economic Dynamics: The Case of Ahmedabad, India - Kotadiya, R. (2020)
In general, urban development projects aim to improve the regional economy and individ-ual livelihoods. Yet, such projects often have a negative impact on some part of the population. Programmes for developing, for example, water supply (dams, reservoirs, irrigation canals, river-front and lakefront development), transportation (roads, highways, canals), mining, power plants and parks and forest reserves often result in development-induced displacement, requiring many people to resettle and rebuild their lives elsewhere (Cernea, 1997b; Jackson and Sleigh, 2000; Robinson, 2003).